Gender Roles and their Influence on the Socio-economic Dynamics of the Community in Jamunar Char Under Manikganj District, Bangladesh - Hossain, Abul; Amin, Sardar Nurul; Kabir, Humayun (Technium Education and Humanities, 2024)
This study explores the influence of gender roles on the socio-economic dynamics of Jamunar Char in the Manikganj District of Bangladesh, focusing on their impact on household decision-making and economic participation. The research aims to assess how gender roles shape decision-making processes within households, with a particular emphasis on women’s involvement in agriculture, fisheries, and other livelihood sectors. The study examines the barriers and opportunities that affect women’s participation in income-generating activities and entrepreneurship. This study uses a mixed-methods approach to explore how gender roles influence socio-economic dynamics in Jamunar Char, Bangladesh. Combining quantitative surveys and qualitative case studies, the research reveals gender-based disparities in economic activities, decision-making, and access to resources. Findings reveal how entrenched gender roles impact economic opportunities and decision-making in the community. This study highlights the critical need for gender-sensitive policies to enhance women’s economic contributions and address the structural challenges they face. By identifying these barriers and opportunities, the research provides valuable insights for developing targeted interventions to promote gender equity and economic resilience in Jamunar Char.